A76 INCOMPLETE RESECTION OF 1-20MM COLORECTAL POLYPS: A SYSTEMATIC REVIEW AND META-ANALYSIS. (26th February 2020) - Djinbachian, R; Iratni, R; Durand, M; Marques, P; von Renteln, D
Abstract: Background: Colonoscopy has been used as a screening or surveillance tool for colorectal cancer (CRC), however, a minority of patients develop post-colonoscopy interval CRC. Incomplete resection of colorectal polyps is thought to be a major cause of post-colonoscopy interval CRC. Aims: We were interested in studying the incomplete resection rate (IRR) of colorectal polyps and factors associated with incomplete resection in a systematic review and meta-analysis. Methods: We conducted a systematic review and meta-analysis using MEDLINE, EMBASE, EBM Reviews, and CINAHL of all studies reporting on IRR of polyps 1-20mm published until March 2019. Exclusion criteria were: Inclusion of IBD cohorts; referrals for difficult polypectomy; polyp size >20mm; endoscopic submucosal dissection; conference abstracts; non-english language. Primary outcome was histologic IRR for polypectomies. Secondary outcomes included IRR for all studies; IRR for polyps 1-10mm and 10-20mm; IRR with or without submucosal injection; IRR based on assessment method of completeness; IRR for different polypectomy methods. Results: 6148 records were identified through initial search and 37 studies with a total of 11962 polyps were included in our quantitative analysis. Histologic IRR for polypectomies (snare and forceps) was 10.54% (95%CI 8.56–12.53). IRR for all included studies was 9.05% (95%CI 7.54–10.56). IRR was lower for polyps 1-10mm than polyps 10-20mm; 8.85% (95%CI 7.27–10.44) vs 18.08% (95%CI 10.30–25.87). IRR was statistically significantly lower when only evaluated using imaging enhanced endoscopy (IEE) (0.69%; 95%CI 0.02–1.35) compared to post polypectomy margin biopsies (7.19%; 95%CI 5.39–8.99). Histologic IRR for snare polypectomy (8.79%; 95%CI 6.96–10.62) was lower than histologic IRR for forceps polypectomy (17.75; 95%CI 10.49–25.01). Conclusions: Incomplete resection of 1-20mm colorectal polyps occurs in a significant proportion of polypectomies. Incomplete resection occurs more frequently in larger (10-20mm) polyps. Visual inspection with IEE after polypectomy underestimates IRR in comparison to post polypectomy biopsies. Snare polypectomy had lower IRR when compared with forceps. Funding Agencies: None